2013
DOI: 10.1111/vop.12112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accelerated collagen cross‐linking for the treatment of melting keratitis in ten cats

Abstract: Accelerated CXL appears to be a valuable option for the treatment of melting keratitis in cats. All the cases have reached a satisfactory outcome despite the individual differences in the conditions prior to the CXL treatment and the variable presence of infectious agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 65 publications
3
54
0
3
Order By: Relevance
“…Signs of melting were absent the day after initiated treatment in both groups. The ability of CXL to stop melting processes in the cornea is consistent with results from previous clinical studies in humans, dogs, and cats . A few clinical reports describe the use of CXL in animals as adjunct to medical therapy for melting keratitis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Signs of melting were absent the day after initiated treatment in both groups. The ability of CXL to stop melting processes in the cornea is consistent with results from previous clinical studies in humans, dogs, and cats . A few clinical reports describe the use of CXL in animals as adjunct to medical therapy for melting keratitis.…”
Section: Discussionsupporting
confidence: 85%
“…CXL increases the bio‐mechanical strength and stabilizes the cornea by forming new cross‐links in the corneal stroma between collagen fibers and between proteoglycan core proteins, thus making it more resistant to melting and bacterial attack through steric hindrance . Hence, it has been used to treat corneal melting in humans, cats, dogs, and horses …”
Section: Introductionmentioning
confidence: 99%
“…The KXL™ System (Avedro, Waltham, Mass., USA) is able to produce a light intensity of 30 mW/cm 2 , enabling ultrafast accelerated CXL with less than 3 min of UVA exposure. It appeared to be effective in a small group of KCN patients when combined with an LASEK procedure [57], and also for treatment of infectious keratitis in cats [58]. …”
Section: Evolution Of Riboflavin: Uva Corneal Collagen Crosslinkingmentioning
confidence: 99%
“…The adverse and cytotoxic effects of high UV-A irradiation has been well documented on skin epithelium or keratinocytes 31. Though there have been studies on the effect of ACXL on animal eyes, there have been none on human LECs 11 32 33. There are, however, some studies that have found transient changes while evaluating the effect of ACXL on the corneal endothelium 34…”
Section: Discussionmentioning
confidence: 99%